2019
DOI: 10.36076/ppj/2019.22.401
|View full text |Cite
|
Sign up to set email alerts
|

The Social and Functional Implications of High- Versus Low-Dose Opioids on Chronic Non-Cancer Pain

Abstract: Background: Chronic non-cancer pain (CNCP) is a major health concern. Opioids may be a useful treatment option, but their use still remains controversial given the significant risks and epidemic of opioid addiction and abuse. There is limited data on whether opioid therapy is an effective treatment option for chronic non-cancer pain. Objective: To assess both physical and emotional dimensions of health for patients on opioid therapy for CNCP by reviewing the 36-Item Short Form Health Survey (SF-36) . Study Des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 13 publications
2
8
0
Order By: Relevance
“…First, and in line with previous research (4), several emotional domains are negatively impacted by opioid usage, while CBP–O’s values were similar to a normative population (Figure 1A,B). Second, and consistent with other findings (5), despite poorer outcomes on these scales, we did not detect dose- or duration-response relationships within the opioid group (Figure 1C,D). Together, points one and two show that, regardless of the dose or duration of their prescription, patients with long-term opioids behaviorally and psychologically differ from patients without opioids.…”
Section: Discussionsupporting
confidence: 92%
“…First, and in line with previous research (4), several emotional domains are negatively impacted by opioid usage, while CBP–O’s values were similar to a normative population (Figure 1A,B). Second, and consistent with other findings (5), despite poorer outcomes on these scales, we did not detect dose- or duration-response relationships within the opioid group (Figure 1C,D). Together, points one and two show that, regardless of the dose or duration of their prescription, patients with long-term opioids behaviorally and psychologically differ from patients without opioids.…”
Section: Discussionsupporting
confidence: 92%
“…lowest dosage of opioids when prescribed for pain. 33,34 Other studies such as those by Spencer et al and Kayani et al have demonstrated, through patient reported outcome scores, that IT decreases pain in comparison to conventional TKA. 35,36 While IT use yielded lower postoperative opioid consumption, our results show a very small difference in opioid consumption that only persists for a short period of time and tapers off by 3 months.…”
Section: Discussionmentioning
confidence: 97%
“…Opioid consumption MME/day is considered to be the lowest dosage of opioids when prescribed for pain 33,34. Other studies such as those by Spencer et al and Kayani et al have demonstrated, through patient reported outcome scores, that IT decreases pain in comparison to conventional TKA.…”
mentioning
confidence: 99%
“…Patients on high doses had lower item scores, indicating poorer health. 32 Opioids may sometimes increase rather than decrease pain. Central sensitization (hyperalgesia) underlies pain chronification generated by high dose and high potency opioids.…”
Section: The Need For Improving the Therapeutic Regimens Of Opioids A...mentioning
confidence: 99%